Profiles and natural drivers of antibiotic resistome in multiple environmental media in penguin-colonized area in Antarctica - Yongpeng Zhang; Bo Zhang; Imtiaz Ahmed; Hanshu Zhang; Yiliang He (Fundamental Research)
Profiles and driving mechanisms of antibiotic resistome in the polar region are important for exploring the natural evolution of antibiotic resistance genes (ARGs). Here, we evaluated the profiles of antibiotic resistome in multiple media on Inexpressible Island, Terra Nova Bay, Antarctica. Average concentrations of ARGs in intracellular DNA (iARGs) among water (3.98 × 106 copies/L), soil (3.41 × 107 copies/kg), and penguin guano (7.04 × 107 copies/kg) were higher than those of ARGs in extracellular DNA (eARGs) among water (1.99 × 104 copies/L), soil (1.75 × 106 copies/kg), and penguin guano (8.02 × 106 copies/kg). It was indicated that the transmission of ARGs across different media occurs with around 77.8% of iARGs from soil and 86.7% of iARGs from penguins observed in water, and 80.7% of iARGs and 56.7% of eARGs from penguins found in soil. Annual inputs of ARGs from Adélie penguins on Inexpressible Island have increased since 1983. Bacitracin, multidrug, and aminoglycoside resistance genes were the main ARGs among water, soil, and penguin guano. Primary medium-risk ARGs associated with human pathogenic bacteria were multidrug resistance genes, and main low-risk ARGs associated with mobile genetic elements (MGEs) were aminoglycoside resistance genes. Antibiotic-resistant bacteria (ARB) from soil and penguins were more phylogenetically related to aquatic antibiotic-resistant mesophiles than aquatic antibiotic-resistant psychrophiles. MGEs, ARB, bacterial diversities, antibiotics, and metals could explain total ARGs between water and soil. Intracellular MGEs were the most significant in-situ driver of iARGs in water, reflecting that horizontal gene transfer could facilitate the spread of ARGs in water. Penguins were important ex-situ drivers of environmental antibiotic resistome, which was linked with risky ARGs between water and soil. These findings highlight the major roles of natural drivers (e.g., MGEs and penguins) in shaping environmental antibiotic resistome in polar areas, improving our understanding of the evolution of environmental microbiome.